2014
DOI: 10.11138/ccmbm/2014.11.1.015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: relevance in dental practice

Abstract: SummaryObjective. The potential role of VDR gene variations in modulating periodontal susceptibility have been a subject of scientific investigations. The aim of this paper is to perform a literature review of the potential correlation between Vitamin D Receptor (VDR) gene polymorphisms and periodontal disease. Materials and methods. A PubMed literature search was made using "vitamin d receptor polymorphisms periodontal disease" as keys words. Only clinical studies in "Humans" as species and "English" as langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
2
28
0
1
Order By: Relevance
“…We found that the ''T'' allele and ''TT'' genotype were associated with an increased risk of gingivitis. Our results are in agreement with previous findings suggesting that the ''TT'' genotype and the presence of the ''T'' allele were associated with chronic periodontal disease in Japanese, Chinese, and Caucasian subjects [Martelli et al, 2014] and also with aggressive periodontal disease [Martelli et al, 2011]. In addition, a meta-analysis of 15 studies including 1,338 cases and 1,302 controls suggested a weak but significantly higher frequency of the Taq I ''TT'' genotype in chronic periodontitis [Deng et al, 2011].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that the ''T'' allele and ''TT'' genotype were associated with an increased risk of gingivitis. Our results are in agreement with previous findings suggesting that the ''TT'' genotype and the presence of the ''T'' allele were associated with chronic periodontal disease in Japanese, Chinese, and Caucasian subjects [Martelli et al, 2014] and also with aggressive periodontal disease [Martelli et al, 2011]. In addition, a meta-analysis of 15 studies including 1,338 cases and 1,302 controls suggested a weak but significantly higher frequency of the Taq I ''TT'' genotype in chronic periodontitis [Deng et al, 2011].…”
Section: Discussionsupporting
confidence: 83%
“…creased transcriptional activity, mRNA stability, and a high serum level of 1,25(OH) 2 D 3 [Martelli et al, 2014]. Several studies evaluated the potential association between this VDR gene polymorphism and an increased susceptibility to periodontitis [Deng et al, 2011].…”
mentioning
confidence: 99%
“…That led to further research focused on the extra-bony effects of vitamin D (Grygiel-Górniak and Puszczewicz 2014;Lips 2006). The VDR encoding gene is located on the chromosome 12 in position 12q13.11 and consists of two promoter regions, eight protein encoding exons, and six untranslated exons (Martelli et al 2014). Some specific VDR gene alleles can influence the action of vitamin D on a cellular level, including calcium metabolism, transcription, cellular divisions and initiation of the immunologic response (Myszka and Klinger 2014;Valdivielso and Fernandez 2006).…”
Section: Vitamin D Mechanism Of Actionmentioning
confidence: 99%
“…The role of vitamin D as a modifier of autoimmunologic conditions of the oral cavity is of considerable importance. Many studies have reported the role of vitamin D as a modifying factor in recurrent aphthous stomatitis (RAS) and related syndromes such as: Behçet's disease and PFAPA (periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis), in Sjögren's syndrome, periodontitis and oral squamous cell carcinoma (OSCC) (Bazrafshani et al 2002;Karatay et al 2011;Khabbazi et al 2014;Martelli et al 2011Martelli et al , 2014Sun et al 2002;Toniato Borges et al 2009). Table 1 presents the results of studies into the impact of vitamin D on oral cavity diseases.…”
Section: The Role Of Vitamin D In the Oral Cavity Diseasesmentioning
confidence: 99%
See 1 more Smart Citation